Inflammatory bowel disease:Pathogenesis - Zhang, Yi-Zhen (World journal of gastroenterology : WJG, 2014)
Inflammatory bowel disease(IBD),including Crohn’s disease and ulcerative colitis,is characterized by chronic relapsing intestinal inflammation.It has been a worldwide health-care problem with a continually increasing incidence.It is thought that IBD results from an aberrant and continuing immune response to the microbes in the gut,catalyzed by the genetic susceptibility of the individual.Although the etiology of IBD remains largely unknown,it involves a complex interaction between the genetic,environmental or microbial factors and the immune responses.Of the four components of IBD pathogenesis,most rapid progress has been made in the genetic study of gut inflammation.The latest internationally collaborative studies have ascertained 163susceptibility gene loci for IBD.The genes implicated in childhood-onset and adult-onset IBD overlap,suggesting similar genetic predispositions.However,the fact that genetic factors account for only a portion of overall disease variance indicates that microbial and environmental factors may interact with genetic elements in the pathogenesis of IBD.Meanwhile,the adaptive immune response has been classically considered to play a major role in the pathogenesis of IBD,as new studies in immunology and genetics have clarified that the innate immune response maintains the same importance in inducing gut inflammation.Recent progress in understanding IBD pathogenesis sheds lights on relevant disease mechanisms,including the innate and adaptive immunity,and the interactions between genetic factors and microbial and environmental cues.In this review,we provide an update on the major advances that have occurred in above areas.